Process optimization of rice husk ash supported catalyst in biodiesel synthesis using response surface methodology approach - Sulaiman N.F.; Leong Y.W.; Lee S.L.; Goh Z.W.; Yahya S.S.M.; Sofiah A.G.N. (Elsevier Ltd, 2025)
Biodiesel is sustainable and biodegradable energy that is synthesized from renewable material consisting of a high capability to replace energy from fossil fuels. This research focused on biodiesel synthesis from waste cooking oil utilizing rice husk ash (RHA) supported catalysts. A series of alkaline earth metal oxide, calcium oxide, and strontium oxide supported on RHA catalyst; CaO/RHA and SrO/RHA catalysts were synthesized via wetness impregnation method with varied calcination temperatures and ratios. It was found that the 10SrO/90RHA (900 C) catalyst produced maximum biodiesel yield (89.97%) over the transesterification process from waste cooking oil, while the catalytic activity of 10CaO/90RHA (800 C) catalyst demonstrated the 83.09% of biodiesel yield. Further analysis on optimization of parameters for transesterification reaction using 10SrO/90RHA (10:90) catalyst revealed that higher biodiesel produced at a reaction temperature of 65 C, catalytic loading of 6 wt%, oil-to-methanol of 1:18 mol ratio and reaction time of 1 h. The optimization for the 10SrO/90RHA (900 C) catalyzed reaction was then verified using response surface methodology (RSM) throughout Box-Behnken design (BBD). The characteristics of the produced biodiesel, under optimal process conditions, comply with the standards set by ASTM D6751 and EN 14214 for fuel quality. ? 2023 Elsevier Ltd